2001
DOI: 10.1053/jhep.2001.28231
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-II type 1 receptor interaction is a major regulator for liver fibrosis development in rats

Abstract: The renin-angiotensin system (RAS) is frequently activated in patients with chronic liver diseases. Angiotensin-II (AT-II) has been suggested to play an important role in liver fibrogenesis. It induces hepatic stellate cell (HSC) proliferation and up-regulates the transforming growth factor 1 (TGF-1) expression via AT-II type 1 receptor (AT 1-R) in vitro. The aim of the present study was to examine the in vivo effect of candesartan (CA), a clinically used AT 1-R blocker (ARB), and perindopril (PE), an angioten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
254
1
4

Year Published

2004
2004
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 365 publications
(275 citation statements)
references
References 41 publications
14
254
1
4
Order By: Relevance
“…We previously reported that simultaneous administration of pig serum and either STI-571 or ACE-I significantly inhibited liver fibrosis development (19,20). The pig serum model is known to induce liver fibrosis without severe inflammation (20).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously reported that simultaneous administration of pig serum and either STI-571 or ACE-I significantly inhibited liver fibrosis development (19,20). The pig serum model is known to induce liver fibrosis without severe inflammation (20).…”
Section: Discussionmentioning
confidence: 99%
“…AT-II is a potent inducer of TGF-ß synthesis through Smad2 in cultured HSCs in vitro (26,27). AT-II induces HSC proliferation and up-regulates TGF-ß expression via the AT1-R pathway (20). The increase in hepatic concentration of TGF-ß induced by bile duct ligation was attenuated in AT1-R knockout mice (28).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are three PPARs, whose general effects are to promote fatty acid catabolism in non-adipose tissue and stimulate fatty acid storage in adipose tissue. 65 Animal models have also suggested a potential role for angiotensin II in the progression of NAFLD to hepatic fibrosis, 66 and the use of angiotensin II type 1 receptor antagonists has been shown to reduce this progression. 67 …”
Section: Hypertension Metabolic Syndrome and Fatty Livermentioning
confidence: 99%